Optimum particle size of corn and hard and soft sorghum grain for nursery pigs and broiler chicks - Healy, B.J.; Bramel-Cox, P.J.; Kennedy, G.A.; Hancock, Joe D.; Behnke, Keith C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 240 weanling pigs (avg initial wt of 11.7 lb) was used to determine the effects of particle size of corn and two sorghum genotypes on growth performance. In addition to the pig feeding experiment, 420 broiler chicks (avg initial wt of .15 lb) were fed the same grain treatments to determine if they were a reliable model for the effects of diet particle size on nursery pig performance. Milling characteristics of the cereal grains were measured. Treatments were corn, hard endosperm sorghum, and soft endosperm sorghum, ground to particle sizes of 900, 700, 500, and 300 µm (geometric mean), with a 3 x 4 factorial arrangement of treatments. In general, reducing particle size increased electrical energy required for milling and decreased production rate. However, there were differences among the grain sources for energy required for milling and production rates, e.g., grinding the sorghums to 500 µm took less energy than grinding corn to 900 µm. In starter pigs, the most efficient gains were achieved at 300 µm for d 0 to 7, 300 to 500 µm for d 0 to 14, and at 500 µm for d 0 to 35. It should be noted that the pig diets were in pelleted form, so problems with bridging and reduced flowability were not a concern with the finely ground grain sources. Overall, pigs fed diets containing corn grew faster, consumed more feed, and were more efficient than those fed sorghum. When compared at their optimum particle sizes, hard and soft sorghum supported ADGs that were 80 and 84%that of corn, and efficiencies of gain that were 96% that of corn. For broiler chicks, reducing particle size of corn below 900 µm did not improve gain to d 21, but grinding sorghum to 500 to 700 µm did improve gain. Efficiency of gain also was improved more with fine grinding of sorghum than corn. Optimum particle sizes for F/G were 300 and 500 µm for hard and soft sorghum, respectively. It is important to note that relative to corn, at 900 p.m feeding values for chicks fed hard and soft sorghums were 92%, but at the optimum particle size for each grain, relative feeding values for hard and soft sorghum were 99% that of corn. These data suggest that sorghums can equal corn in feeding value for broiler chicks when milled to their optimum particle size, and that as pigs and chicks get older, optimum particle size increases. However, starter pigs fed corn had 15 to 20% greater ADG and 4% greater efficiency of gain than pigs fed the sorghums.
Keywords: Swine; Particle size; Corn; Sorghum; Endosperm hardness; Starter; Broiler chicks